2014
DOI: 10.1007/s11356-014-2721-2
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of naproxen in water under simulated solar radiation: mechanism, kinetics, and toxicity variation

Abstract: The main objective of this study was to investigate the degradation mechanism, the reaction kinetics, and the evolution of toxicity of naproxen in waters under simulated solar radiation. These criteria were investigated by conducting quenching experiments with reactive oxygen species (ROS), oxygen concentration experiments, and toxicity evaluations with Vibrio fischeri bacteria. The results indicated that the degradation of naproxen proceeds via pseudo first-order kinetics in all cases and that photodegradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 36 publications
0
18
0
3
Order By: Relevance
“…Moreover, the toxicity of its dimers is stereo-dependent (DellaGreca et al 2004). Ma et al (2014) reported that during simulated solar radiation, the generated product of naproxen photodegradation was more toxic than the parent compound. Its toxicity is probably connected with a loss of the chemical moieties of naproxen resulting in a lower steric effect and easier penetration into the cells of Vibrio fischeri (Ma et al 2014).…”
Section: Occurrence Of Naproxen In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the toxicity of its dimers is stereo-dependent (DellaGreca et al 2004). Ma et al (2014) reported that during simulated solar radiation, the generated product of naproxen photodegradation was more toxic than the parent compound. Its toxicity is probably connected with a loss of the chemical moieties of naproxen resulting in a lower steric effect and easier penetration into the cells of Vibrio fischeri (Ma et al 2014).…”
Section: Occurrence Of Naproxen In the Environmentmentioning
confidence: 99%
“…Ma et al (2014) reported that during simulated solar radiation, the generated product of naproxen photodegradation was more toxic than the parent compound. Its toxicity is probably connected with a loss of the chemical moieties of naproxen resulting in a lower steric effect and easier penetration into the cells of Vibrio fischeri (Ma et al 2014). However, it was also demonstrated that the solar photocatalysis of naproxen partially reduces its acute toxicity (Jallouli et al 2016;Marotta et al 2013).…”
Section: Occurrence Of Naproxen In the Environmentmentioning
confidence: 99%
“…In the past few years, several studies have been conducted on the subject of NAP removal from water. These studies used different treatment methods and remediation technologies such as photo-degradation, ozonation, ultra-sonication, gamma irradiation, nanofiltration [7][8][9][10][11][12][13]. Benitez et al [14] showed that O 3 /H 2 O 2 was the most successful oxidative system for NAP (1 lM) degradation in ultrapure water (UP) with an achieved degradation rate of about 2.64 Â 10 À4 M À1 s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Two years later, Marotta et al [10] (1 lM) and found better results in oxic solutions rather than under anaerobic conditions. In 2014, Ma et al [7] demonstrated that NAP (43 lM) photo-degradation by direct solar photolysis and by self-sensitization via reactive oxygen species was effective. However, the adopted process yielded some intermediate products more toxic than NAP.…”
Section: Introductionmentioning
confidence: 99%
“…La banda de mayor energía localizada alrededor de los 230 nm asociadas a las transiciones → * del grupo aromático, disminuye homogéneamente con la banda del grupo carboxilo, revelando que el proceso de oxidación fotocatalítica además de generar especies intermediarias, genera el rompimiento del anillo aromático, sugiriendo la posible mineralización del compuesto contaminante. El ligero corrimiento batocrómico (corrimiento hacia el rojo/desplazamiento a longitudes de onda mayores y de menor energía) en las bandas de absorción de NPX desde los primeros 30 min de reacción, está asociado a productos intermediarios originados durante la desmetilación y descarbolilación de NPX, conduciendo a la formación de compuestos solubles y/o volátiles de alto y bajo peso molecular (Figura 3.26b)).Entre los compuestos de alto peso molecular se han observado: ácido 2(6-hidroxinaftalen-2il)propiónico, 1(6-metoxiftalen-2-il)etanona, 1(6-metoxiftalen-2-il)etanol, después de 120 min de reacción[119,121] y entre los de bajo peso molecular podemos encontrar metano, etano, alcoholes derivados, ácido alifático y cetonas[122].…”
unclassified